The Influence of Student Characteristics, Student Readiness to Learn, Learning Concentration, Teacher Teaching Quality, and Educational Costs on the Learning Achievement of Class X E Students in Economics Subject - Guspina Rinawati Sababalat; Jimi Ronald; Lovelly Dwinda Dahen (Global Action and Education for Society, 2026)
This research aims to determine: The influence of student characteristics, student readiness to learn, learning concentration, teacher teaching quality, and education costs on the learning achievement of class X E students in Economics at SMA Negeri 2 Sipora, Mentawai Islands Regency.